The role of near and far knowledge transfer on the job performance of the employees in MNCs - Salazar, Paulina (My University, 2024)
Nowadays the main economic resource for companies is organizational knowledge, it gives competitive advantage and value to productivity and innovation. However, the knowledge that is not applied does not become productive and stays in information form. The management of knowledge includes the process of being transferred and applied. This thesis aims to explore how the utilization of different dimensions of knowledge transfer between employees reflects on their job performance. This research focuses on a dichotomy, near and far knowledge transfer, that depending on the form it can affect the performance of the individual on their job performance. The main findings of the empirical research complement the synthesis of the literature review of knowledge transfer between employees were three, first the inclusion of a hybrid knowledge transfer, second, include the motivation as part of the individuals involved in the exchange of knowledge and last, include important aspects or characteristics that are part of the knowledge transfer and affect the quality and efficiency of the transference.
Keywords: organizational knowledge, knowledge transfer, dimensions of knowledge transfer, near knowledge transfer, far knowledge transfer, job performance, task performance, contextual performance